THE ANALYSIS OF THE STUDENTS’ ANXIETIES IN LEARNING ENGLISH: THE CASE OF A PRIVATE ISLAMIC JUNIOR HIGH SCHOOL - Aam Alamsyah; Ayu Made Padma Saraswati Dewi (Acitya: Journal of Teaching and Education, 2021)
The present study analyzed the students’ anxieties in learning English. The study was conducted in a case study involving 44 respondents of a privately funded Islamic junior high school located in Tangerang. The respondents were recruited purposively. Due to the application of no physical contact during the class, a questionnaire was the only instrument used in the present study. The finding indicated that the primary cause of the students’ anxieties was their learning problem. In addition, the students’ problems were mainly caused by the students’ inability to cope with some learning materials. The finding also indicated that speaking and writing were the most problematic skills which could probably generate anxieties. Lastly, the students also considered that their teachers and the way they taught were the main factors that could trigger anxieties in learning English. Some suggestions are given to overcome this matter.